Human lymph node degeneration in the thoracic region: A morphometric and immunohistochemical analysis using surgically obtained specimens - Jin, Zhe-Wu; Aoki, Masaya; Ueda, Kazuhiro; Kamimura, Go; Takeda-Harada, Aya; Murakami, Gen; Sato, Masami (Frontiers in Physiology, 2022)
Lymph node degeneration was examined in 539 mediastinal and intrapulmonary nodes removed from 78 patients, aged 49-82 years, without cancer metastasis. Medullary sinus hyalinization observed in 36.2% of the hilar and 38.5% of the interlobar nodes. Early and smaller lesions were eosinophilic and factor VIII-positive, whereas advanced and large lesions contained a bulky mass of collagenous fiber bundles with few slender cells positive for smooth muscle actin (SMA) and factor VIII, as well as anthracotic macrophages. Subcapsular sinus hyalinization, observed in 4.3% of hilar nodes, was detected as a thick fibrous layer (over 0.2 mm) between the surface cortex and the thickened capsule. The fibrous layer contained SMA-positive slender cells, whereas the thickened capsule contained fibers positive for elastin and factor VIII. These hyalinization lesions occupied 3.6% and 0.8% of the sectional areas of hilar and lower paratracheal nodes, respectively. Areas of early and small cortical degeneration, surrounded by fibers positive for SMA and vimentin, did not contain lymphocytes and macrophages, but contained abundant small stromal cells. Silver staining suggested that advanced cortical degeneration was composed of collagen fibrils other than type I. Fatty tissues, seen in 47.8% of hilar nodes, often extended into and replaced medullary sinus tissue. Island-like remnants of medullary sinuses in areas of fatty degeneration contained various stromal cells positive for SMA, elastin, factor VIII and/or CD34. These degenerative morphologies, however, did not correlate with either age or smoking index. The present cortical degeneration usually seemed to follow hyalinization, but both were likely to occur independently.